Preparation and photocatalytic activity of TiO2-exfoliated graphite oxide composite using an ecofriendly graphite oxidation method - Vanessa Zanon Baldissarelli (2015)
A simple and effective stepwise-method was developed to produce expanded exfoliated graphite oxide(EGO). Using a combination of ozone exposure and thermal treatment we demonstrate that a graphitesurface can be modified to generate a graphene-like surface containing oxygen and sp3 carbon. Thisexpanded exfoliated graphite oxide is useful for the production, through thermal treatment, of photocatalytic TiO2-EGO composites which are more active than those produce by the Hummers method. Thephotocatalytic activity of TiO2-EGO in methylene blue (MB) bleaching under UV light is enhanced incomparison with TiO2 P25.